SYNTHESIS OF ANTIMALARIAL 3-(2-HYDROXYETHYL)-2-METHYL-1,10-PHENANTHROLINE-4-OL FROM 8-AMINOQUINOLINE - Ruslin Hadanu; Chairil Anwar; Jumina Jumina; Iqmal Tahir; Mustofa Mustofa (Universitas Gadjah Mada, 2004)
It has been conducted the synthesis of 3-(2-hydroxyethyl)-2-methyl-1,10-phenanthroline-4-ol was carried out from 8-aminoquinoline which are expected to posses antimalarial activity. The experiment perfomed consisted of two steps i.e (1) reaction of 8-aminoquinoline with 2-acetyl-butyrolactone and (2) cyclization of the resulted 3-[1-(quinolin-8-ylamino)-ethylidene]-4,5-dihydro-furan-2-one. The reaction of 8-aminoquinoline with 2-acetyl-butyrolactone was performed in toluene at reflux for 6 hours in the presence of p-toluensulfonic acid as catalyst. This reaction gave 3-[1-(quinolin-8-ilamino)-etiliden]-4,5-dihidro-furan-2-on in 60.6% yield. The cyclization of 3-[1-(quinoline-8-ylamino)-ethyliden]-4,5-dihydro-furan-2-one was conducted in cloroform at reflux for 4 hours in the presence of H2SO4 as catalyst and also tween 80 as transfer phase catalyst to give 3-(2-hydroxy-ethyl)-2-methyl-1,10-phenanthroline-4-ol in 76.2% yield. Identification of the products were carried out by means of infra red (IR) spectroscopy, proton nuclear magnetic resonance (1H-NMR) spectroscopy, and mass spectroscopy (MS).